A case for folletian interventions in public universities. (8th February 2019) - Pelly, Robert Duncan M.; Boje, David
Abstract : Purpose: The purpose of this paper is to illustrate the ideological impasses between educationally minded faculty and neoliberal oriented university administrators. To bridge and benefit from these two perspectives, Follettian integration is introduced. Specifically, the ensemble learning theory (ELT) and entrepreneurship centers are illustrated as Follettian interventions and their reasons for success are discussed. Design/methodology/approach: This paper is theoretical, but provides ethnographic anecdotes of the problems occurring during the rise of neoliberalism and academic capitalism in the public university. The successful use of the ELT and entrepreneurship centers is likewise explored anecdotally. Findings: This paper illustrates the benefits of utilizing the ELT and entrepreneurship centers in two different university settings. Research limitations/implications: While the sample sizes of this paper are small, the anecdotal examples provide the basis for reasoning by analogy. Practical implications: This work illustrates two possible Follettian interventions that serve as a guide to assist university administrators and faculty to find common ground and better serve students and university communities. Originality/value: The rise of academic capitalism and neoliberalism has devalued education and resulted in poorer educational outcomes and a modern generation with less intellectual capital. This is one of the first papers to utilize Mary Parker Follett's theories of education and apply them to the impending identity crisis of the public university. The result is a win-win for both neoliberal administrators and faculty in the face of an impending identity crisis for the public university.